Estimating the effects of land-use and catchment characteristics on lake water quality: Irish lakes 2004-2009 - Curtis, John; Morgenroth, Edgar (Statistical and Social Inquiry Society of Ireland, 2013)
This paper attributes the variation in water quality across Irish lakes to a range of contributory factors such as human population, septic tanks, urban waste water treatment, phosphorous excreted by livestock, as well as catchment soil and geology. Both linear and non-linear quadratic models were estimated in the analysis, which attempts to account for point and non-point sources of pollution affecting water quality in 216 lake catchments. The models show a clear link between activities within lake catchments (e.g. agriculture, population, etc.) and lake water quality, finding that the relationship is neither simple nor linear. The analysis also shows that it is important to account properly for the type of and intensity of land-use particularly in relation to agriculture.
Keywords: lake water quality; land-use; chlorophyll concentration; 314.15